Emergence of the invasive malaria vector Anopheles stephensi in Khartoum State, Central Sudan - Ahmed, Ayman; Khogali, Rua; Elnour, Mohammed-Ahmed B.; Nakao, Ryo; Salim, Bashir (Parasites & vectors, 2021)
The emergence of the Asian invasive malaria vector, Anopheles stephensi , has been identified in Khartoum, the capital city of Sudan. This is the first report that confirms the geographical expansion of this urban mosquito into Central Sudan. We urgently recommend the launch of a national entomological survey to determine the distribution of this invasive disease vector and to generate essential information about its bionomics and susceptibility to available malaria control measures. Graphical Abstract